2021
DOI: 10.3390/pharmaceutics13030416
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4-Au Core-Shell Nanoparticles as a Multimodal Platform for In Vivo Imaging and Focused Photothermal Therapy

Abstract: In this study, we report the synthesis of gold-coated iron oxide nanoparticles capped with polyvinylpyrrolidone (Fe@Au NPs). The as-synthesized nanoparticles (NPs) exhibited good stability in aqueous media and excellent features as contrast agents (CA) for both magnetic resonance imaging (MRI) and X-ray computed tomography (CT). Additionally, due to the presence of the local surface plasmon resonances of gold, the NPs showed exploitable “light-to-heat” conversion ability in the near-infrared (NIR) region, a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 83 publications
1
28
0
Order By: Relevance
“…The presence of Fe 3 O 4 nanoparticles is sufficient to reduce the net magnetization of the samples. The novelty of this work is that the magnetization of our samples is higher than all the previous trials made in this system [31][32][33][34]. In addition, comparison of coercivity and saturation magnetization with literatures is shown in Table S1.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The presence of Fe 3 O 4 nanoparticles is sufficient to reduce the net magnetization of the samples. The novelty of this work is that the magnetization of our samples is higher than all the previous trials made in this system [31][32][33][34]. In addition, comparison of coercivity and saturation magnetization with literatures is shown in Table S1.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, Au shell can reduce the magnetic particle-particle interactions between Fe particles leading to better dispersion in the biological solutions (Figure 1a). Iron gold core shells were successfully designed using wet chemical methods in previous reports with a high ratio of iron oxides impurities, which hinder the magnetic capabilities of the material and some of them reported their ability for photothermal hyperthermia [32][33][34]. Here, we used the same wet chemical method with more controlled precautions to design pure Fe metal coated with Au nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In another example, Caro et al synthesized Au coated SPIONs and capped with PVP (Fe@Au NPs) by a seed-mediated growth chemical method. In the study, the NPs showed a multimodal activity as contrast agents for MRI, X-ray CT and as possible image-guided PTT, thus indicating the potential development of the platform as theranostics agents [ 195 ]. Similar strategies to Au and Ag NPs are employed for the surface functionalization and stabilization of the SPIONs and are depicted in Figure 3 .…”
Section: Nano-based Building Blocksmentioning
confidence: 99%
“…As the dose delivered by ionizing irradiation interacting with high-Z material can be amplified via an enhancement of the photoelectric effect, the release of so-called Auger electrons and X-ray fluorescence induced electrons can increase the lethal effect of irradiation at lower doses. Gold, with an atomic number of 79, is the most studied material in this respect, as its high-Z value makes AuNPs prime candidates as contrast agents for computed tomography (CT) [6][7][8][9]. Regulla et al [10,11] tested the effect of a gold foil and the experimental as well as simulation data showed a dose enhancement factor of up to 150 in the first tissue layer close to the gold foil.…”
Section: Introductionmentioning
confidence: 99%